2018
DOI: 10.1111/jog.13600
|View full text |Cite
|
Sign up to set email alerts
|

Fetoscopic laser photocoagulation for twin–twin transfusion syndrome

Abstract: The aim of this study was to review fetoscopic laser photocoagulation (FLP), which ablates placental vascular anastomoses to treat twin–twin transfusion syndrome (TTTS). A review of studies reporting on the procedures, outcomes, complications and nonconventional applications of FLP for TTTS was conducted. FLP has been established as the primary treatment for monochorionic twin pregnancy associated with TTTS at 16–26 weeks. FLP is the only therapy that directly addresses the underlying pathophysiology. The rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 62 publications
(76 reference statements)
3
26
1
Order By: Relevance
“…The Victorian Fetal Therapy Service (VFTS) is a three-centre collaboration between Monash Health, Mercy Hospital for Women (MHW) and The Royal Women’s Hospital (RWH), with surgery conducted at Monash Health. Reported outcomes have been consistent with international experience [ 14 , 17 , 20 , 21 ], with 68% overall infant survival, and survival of one or more twin/s in 86% of gestations treated.…”
Section: Introductionsupporting
confidence: 79%
“…The Victorian Fetal Therapy Service (VFTS) is a three-centre collaboration between Monash Health, Mercy Hospital for Women (MHW) and The Royal Women’s Hospital (RWH), with surgery conducted at Monash Health. Reported outcomes have been consistent with international experience [ 14 , 17 , 20 , 21 ], with 68% overall infant survival, and survival of one or more twin/s in 86% of gestations treated.…”
Section: Introductionsupporting
confidence: 79%
“…MD twins with AFD who do not meet the TTTS criteria but who have abnormal umbilical Doppler parameters have a high risk for poor outcomes . Moreover, in a systematic review, MD twins with type II selective IUGR (defined as persistently absent/reversed umbilical artery flow pattern in the smaller infant) were found to be at high risk for abnormal postnatal brain imaging (intraventricular hemorrhage or periventricular leukomalacia) compared with those with type I (12% vs 2.5%) . In contrast, both of the present infants did not have umbilical Doppler abnormalities but did have poor prognosis with brain abnormalities in the larger infant; therefore, this is considered a rare case.…”
mentioning
confidence: 60%
“…Although not a TTTS criterion, amniotic fluid discordance (AFD) or selective intrauterine growth restriction (IUGR) also contributes to poor prognosis. 1,2 Herein, we report the case of the larger infant in MD twins with AFD and selective IUGR who presented with unique cerebral hemorrhagic infarction.…”
mentioning
confidence: 99%
“…Adverse outcome was defined as the occurrence of IUFD. The definitions of TTTS, sIUGR, and TAPS are described in the Appendix (Tables ) as per the International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) practice guidelines . Discordant ratio of birth weight (DRBW) was defined with two live births, calculated using the following formula: ([larger BW−smaller BW]/larger BW) × 100% as described by Hartley et al The prevalence of DRBW more than 25% (BWD 25%) was confirmed.…”
Section: Methodsmentioning
confidence: 98%